Acute effects of proprioceptive neuromuscular facilitation stretching on rectus femoris muscle stiffness: a dose-response shear-wave elastography study - Kranjc, Sara; Fink, Mojca; Nakamura, Masatoshi; Kozinc, Žiga (Frontiers in Physiology, 2025)
IntroductionProprioceptive neuromuscular facilitation (PNF) stretching is widely used to increase range of motion, but its underlying mechanisms are not well understood. This experimental, parallel group design study investigated the acute effects of PNF stretching on rectus femoris muscle stiffness and explored a potential dose-response relationship.MethodsThirty healthy young adults (23 females, 7 males) were randomly assigned to either a PNF stretching group (n = 15; 22.96 ± 2.2 years) or a control group (n = 15; 23.3 ± 2.1 years). Rectus femoris stiffness was measured using shear-wave elastography (Resona 7, Mindray, China) at two locations (distal and proximal) before and after the second, fourth, and sixth sets of PNF stretching. The protocol involved six sets, each with three 10-s stretches and 5-s maximal contractions.ResultsThe results indicate that PNF stretching had no statistically significant effect on muscle stiffness, with no main effects of group (F = 0.05; p = 0.830) or time (F = 0.545; p = 0.653), and no significant interactions. However, the proximal location showed a substantially higher shear modulus compared to the distal location (F = 63.6; p < 0.001; η2 = 0.69), independent of group or time.DiscussionThese findings highlight a location-specific difference in muscle stiffness that was unaffected by the intervention. In conclusion, PNF stretching did not acutely reduce rectus femoris stiffness compared to passive rest, regardless of the number of stretching sets performed. Further research is needed to understand the muscle-specific effects of PNF stretching.